Chromoendoscopy Versus Standard Colonoscopy for Detection of Nonpolypoid Dysplasia in Patients With Inflammatory Bowel Disease - Sekra, A; Schauer, C; Mills, L; Vandal, A; Rose, T; Lal, D; Ogra, R (New Zealand Medical Association (NZMA), 2018)
AIM: Inflammatory bowel disease (IBD) is associated with an increased risk of colorectal cancer. Studies show that chromoendoscopy (CE) can increase the detection of dysplasia at surveillance colonoscopy, compared to standard white light endoscopy (WLE). We performed a retrospective cohort study to compare standard WLE to CE with targeted biopsies in detecting nonpolypoid dysplasia in IBD patients undergoing surveillance colonoscopy at a single tertiary centre. METHOD: Data was collected on 110 consecutive patients with IBD who underwent surveillance colonoscopy from 1 August 2015 to 31 July 2017 at Counties Manukau District Health Board, Auckland. Patients had either WLE or CE. Patient characteristics, endoscopic and histologic descriptions were reviewed. Rates of dysplasia detection by the di erent endoscopic techniques were compared using an exact Poisson test. RESULTS: 76/110 (69%) had WLE (mean age 56y; median disease duration 18y) and 34/110 (31%) had CE (median age 59y; median disease duration 19y). Nonpolypoid dysplasia was detected in 0/76 (0%) patients who had WLE. Seven nonpolypoid dysplastic lesions were detected in 4/34 (11.8%) patients who had CE. Dysplasia pick up rate was significantly higher in the CE group with a risk di erence of 11.8%, 95% confidence interval (0.93, 22.59), p=0.008. Dysplasia detection rate per patient was also significantly higher in the CE group with a rate difference of 20.6 lesions per 100 patients, 95% confidence interval (5.3, 35.8), p=0.0003. As expected, there was no di erence between the number of polypoid dysplastic lesions found between the two groups (p=0.12). CONCLUSION: In our cohort of IBD patients undergoing surveillance colonoscopy, CE with targeted biopsy is associated with a significantly increased nonpolypoid dysplasia detection rate when compared to WLE. These results are comparable to studies performed in the rest of the world.